Keunggulan Teknologi Bangunan Rumah Panggung Pada Rumah Sederhana Sehat Perumahan Citra Indah Kecamatan Jonggol-Cileungsi Kabupaten Bogor - Rita Laksmitasari Rahayu; Soepardi Harris (Faktor Exacta, 2017)
Some of the Rumah sederhana Sehat (RsS) of less than 30m2 type has been in accordance with the Simple Healthy House Development Technical Guidelines (RsSehat), but the growing need to make room on the RsS house increases the space of the house. It shuts down the entire plot available and creates discomfort for the occupants. The study was conducted related to the environmental aspects of natural and man-made with thermal comfort factors, water infiltration on plots, and the line of fire evacuation taken into account. Direct observation on the landed houses in clusters of Palem Citra Indah, Bukit Jonggol subdistrict, Bogor regency by comparing several stage house data in Bogor. Data analysis model used is the constant comparative method. In landed houses and there is less qualified thermal comfort, very bad water catchment area, and did not notice the fire evacuation route. The whole stage houses has KDB below 40%, there is a fire evacuation paths, and good thermal comfort.